(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Kalanchoe pinnata is a perennial plant that is widely used in the folklore treatment of kidney and gall stones and urinary insufficiency. The present study aims to evaluate the potential toxicity of the leaf extract of this plant upon acute and sub-acute (28 day) exposure in Wistar rats when administered orally. In Acute oral toxicity(n=3) Female Wistar rats were treated with a single dose of 2000mg/kg b.wt and observed for 14 days and Sub-acute toxicity(n=6) Male and Female Wistar rats were treated with the dose of 500 and 1000mg/kg b.wt of leaf extract for 28 days consecutively. No mortality, morbidity or adverse clinical signs of toxicity were observed during the experimental period. No significant changes in the body weight was observed. Gross necropsy did not indicate any treatment-related pathological changes in any of the animals in the acute and sub-acute toxicity studies. Histopathology of the Liver, Heart and Kidney did not show any remarkable lesions that could be related to the administration of the leaf extract. Ethanolic leaf extract of Kalanchoe pinnata is relatively safe with an LD50 value greater than 2000 mg/kg. From the sub-acute study, the no-observed adverse effects level (NOAEL) of the extract can be derived as 1000 mg/kg b.wt in male and female Wistar rats.